Pemberdayaan SDM Industri melalui Pelatihan Pendampingan Berbasis Evaluasi Importance – Performance Analysis di PT XYZ - Tyas Eka Kurnia; Fajri Azmi Arrasyid; Amenda Septiala Tarigan; Nanang Alamsyah (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
PT XYZ, a company operating in the manufacturing, telecommunications, and financial services sectors, faced a need to enhance its human resource capabilities regarding the systematic evaluation of job satisfaction—a foundation for formulating employee development strategies. Previously, job satisfaction evaluations had not utilized a method capable of identifying improvement priorities in a structured manner. This community service initiative aimed to assist the partner in implementing the Importance–Performance Analysis (IPA) method as a tool for evaluating job satisfaction and formulating human resource development recommendations. The implementation process involved coordinating and identifying the partner's needs, introducing concepts of job satisfaction and the IPA method, providing guidance on developing and administering evaluation instruments, analyzing results collaboratively with the partner, and formulating follow-up recommendations. The activity was evaluated by analyzing the IPA mapping results across ten job satisfaction indicators. The assistance provided enabled the partner to understand the application of the IPA method as an internal evaluation tool and to identify attributes requiring priority improvement: knowledge of job, productivity, and leadership qualities. Additionally, attributes such as quality of work, adaptability, judgment, interpersonal relations, and performance fell into the category requiring maintenance. This initiative benefited the partner by enhancing their capacity to independently conduct job satisfaction evaluations and formulate more targeted human resource development programs based on the evaluation results.